Recurrent restorying through language teacher narrative inquiry. (November 2021) - Golombek, Paula R.; Johnson, Karen E.
Abstract: We propose a novel methodology for analyzing language teacher narrative inquiry : recurrent restorying, teachers engaging in narrative analysis and re-storying of their own previously storied learning-to-teach experiences, concepts, and self-understandings as unbounded by time and place. In recurrent restorying, language teacher narrative inquiry is a tool-and-result activity (Vygotsky, 1978) in that the variously storied learning-to-teach experiences within a teacher education program are the narrative data, and the teachers themselves are the data analysts who trace their own professional development. We present two preservice teachers' return to their previously storied experiences of learning-to-teach in an MA TESL program and work through the process of recurrent restorying to trace their conceptual development as language teachers. We argue that recurrent restorying has dual transformative powers; it maximizes internalization (the process through which social relations and cultural artifacts take on psychological status for individuals) by allowing teachers to trace how external forms of social interaction serve as the source of their internalized psychological tools for thinking; and it concretizes the mediational role that engagement in recurrent restorying plays in enabling teachers to articulate their conceptual development as teachers (person) and in their teaching (activity).